Home and Office Blood Pressure Monitoring in Renal Transplant Recipients - Rebecca Sberro-Soussan; Marion Rabant; Renaud Snanoudj; Julien Zuber; Lynda Bererhi; Marie-France Mamzer; Christophe Legendre; Eric Thervet (Journal of Transplantation)
Background. Arterial hypertension in renal transplant recipients (RTR) is associated with increased morbid mortality. In the general population, home blood pressure monitoring (HBPM) was found to be superior to office blood pressure (OBP) in identifying true hypertensive patients. The aim of this study was to investigate HBPM for the assessment of blood pressure profile in RTR. Methodology and Principal Findings. We included prospectively 87 stable RTR. Sitting OBP was measured during the outpatient clinic. HBPM was performed by measuring BP every morning and night for 4 days. The accepted limits for the OBP and HBPM, were respectively, 140/90 mmHg and 135/85 mmHg. Patients were classified as “normotensive,” “uncontrolled,” “white-coat hypertensive” and “masked hypertensive”, (OBP below the limit and HBPM above). During the study, 81 patients (55 males, age 48.5±14 years) were available for analysis. The mean OBP and HBP were 138/83±14/10 mmHg and 133/79±14/8 mmHg; 29% of patients were uncontrolled, 28% normotensive, 21% white coat, and 21% masked hypertensive. Age, glycemia, and number of antihypertensive drugs were associated with hypertension. Conclusion and Significance. In RTR, HBPM is well accepted and better define BP profile since there is 42% discrepancy between OBPM and HBPM. Whether this discrepancy is associated with worst outcome in the long term remains to be demonstrated.